Assessment of Heavy Metals Pollution for Cultivated Soils, Irrigated by Several Irrigation Waters Varying in their Qualities in Al-Hassa Oasis, Kingdom of Saudi Arabia - M. S. Mohammed; A. A. M. Sallam; S. M. Aleid (Current Topics in Agricultural Sciences Vol. 4, 2021)
Twenty-four composite surface soil samples (0-30cm depth) representing cultivated soils irrigated for long-term (more than fifteen years) with different irrigation water qualities:(i-ground water (GW), ii-ground water + agricultural drainage water (DW), iii-ground water + tertiary treated wastewater (TTWW) and iv-ground water, (GW) + agricultural drainage water, (DW) + tertiary treated wastewater, (TTWW), were analyzed for their contents, from Cu, Mn, Fe, Zn, Co, Cd, Pb, As and Ni. The results showed that, these contents can be arranged in the following descending order: Fe > Cu >Mn>Zn> Ni >Pb> Co > As > Cd. Generally, the different irrigation water qualities can be arranged according to their effects on total heavy metal contents in the soils in the following order:(GW+DW+TTWW) >(GW+TTWW)> (GW+DW)> (GW). Based on the geo-accumulation index, Igeo values for Mn, Fe, Co, and Cd, the soil irrigated with groundwater is uncontaminated with these elements. On the other hand, Igeo values for Cu, Zn, Pb, and Ni are > 0 and <1, indicating that the soil is uncontaminated to moderately contaminated with these elements. In general, Igeo values for the soil irrigated with (GW+ DW+TTWW) showed patterns of heavy metals contamination similar to those of the soils irrigated with(GW+TTWW) and those irrigated with (GW+DW) but with different levels. Based on the Enrichment factor (EF) the studied soils are significantly contaminated with Cu, Ni, and Zn due to irrigation with, ground water, Cu, Ni, Pb, and Zn in the soil irrigated with (GW+DW), Cu, Pb, Zn, Ni, and As in both soils irrigated with (GW+TTWW) and (GW+ DW+TTWW). The results reveal that the EF mean values of heavy metals in the studied soils irrigated with different irrigation water qualities, can be arranged in the following descending order:(GW+ DW+TTWW)> (GW+TTWW) > (GW+DW) > (GW). The objectives of the present study were to: (1) assess heavy metal contamination of agriculture cultivated soil irrigated with different irrigation water qualities in Al-Hassa Oasis, Saudi Arabia using three approaches, namely; the geo accumulation index (Igeo), Enrichment Facto (EF) and Pollution Index (PI).